Acesso e utilização dos serviços de atenção básica à saúde no bairro Noal, área urbana do município de Santa Maria/RS - Savian, Paloma da Silva (2019)
The Unified Health System (SUS) is the result of the movement idealized by the Brazilian Sanitary Reform. This reformist ideology understood the need to reorient the prevailing medical-privative assistance model to a universalist care model based on Basic Health Care (BHC). Brazil adopted Basic Health Care as a strategy for the reorganization of its health system, a move that was completed in 1988 with the promulgation of the Federal Constitution and the creation of the Unified Health System (SUS). This model of health care was implemented as a Family Health Program in 1994, achieving rapid territorial expansion and increasing access to health services. This model of care assumes that each Family Health team (ESF) should be responsible for a geographically delimited public with an assigned clientele. However, far from the dream of the constituents and the health reform movement, the consolidation of health as a right of every citizen is not yet a reality, since the evidence on inequalities and inequities in health conditions is remarkable. The master's research has as main objective to understand the spatial dynamics of the access and the use of the Basic Attention services to the SUS health. This is a cross-sectional, population-based study conducted in the Noal neighborhood, in the urban area of Santa Maria, Rio Grande do Sul, Brazil.The instrument of data collection will be a standardized questionnaire applied in the form of an interview. The target population of the study are individuals aged 18 and over, of both sexes, living in the Noal neighborhood. The database will be analyzed in Geographic Information System (GIS) and using spatial statistics operations. The results indicate that users of the Lídia Family Health Strategy (FHS) are more likely to have a regular source of health care compared to those not covered by the FHS. Of those who reported looking for the FHS service, the use was mainly made for the control of chronic diseases. No geographical barriers were observed that could prevent access to and use of health services, both in FHS Lídia and in the Basic Social Health Unit, Centro Social Urbano (CSU)